Making instagram film to improve sales of wooden and bamboo basic products products sanggar arts nggara simbelin in village Lingga Karo district - Purba, Parlindungan; Sinulingga, Samerdanta; Pohan, Riko Andika Rahmat Pohan; Siregar, Achmad Husein (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
In the context of tourism, supporting facilities such as shops / souvenir businesses has a strategic position in its existence, because it is ‘secondary travel needs’. This secondary travel needs are produced and marketed by a an art studio called Nggara Simbelin art studio located in Lingga village. This art studio is the supporting for tourism existence in the Karo District to date, which has been providing souvenirs based on wood, however this souvenir business has various problems. One of which is marketing,it is weak so that it sometimes results in a build-up of goods of those souvenir in the warehouse. During the 4.0 industrial revolution, information is not only as needs however it has become a primary need for millennials today, and nature and local creativity are highly valued interests for tourists. Therein lies the opportunity, where in this research will be packed as an advertisment in the form of a film teaser to support business marketing souvenir so that it can become a commodity information for millennial tourists who visited tourist sites in the Karo District. The movie teaser is expected to increase sales of souvenir products made from wood from Nggara Simbelin art studio in Lingga Village. This study uses the science of phenomenology, participant observation techniques, with data analysis: (1) data reduction; (2) presentation data; and (3) drawing conclusions / verification. The making of tourism films in this study uses 2 theories, a secondary theory, namely: the theory of film making with 3 working indicators: pre-production, production and postproduction of films, while the primary theory is: film theory as a tourism promotion media with 4 working indicators: color, features, properties and ratios. The results of the application of the seven working indicators of the theory produces a true tourism film as a tourism promotion media. From this research, the next study we will examine how is the impact of this advertisment on the sale of wooden souvenirs for the Nggara Simbelin art gallery.